2006
DOI: 10.3346/jkms.2006.21.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Complications After Hematopoietic Stem Cell Transplantation

Abstract: Despite advanced effective prophylaxes, pulmonary complications still occur in a high proportion of all hematopoietic stem cell recipients, accounting for considerable morbidity and mortality. The aim of our study was to describe the causes, incidences and mortality rates secondary to pulmonary complications and risk factors of such complications following hematopoietic stem cell transplantation (HSCT). We reviewed the medical records of 287 patients who underwent either autologous or allogeneic HSCT for hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
4
20
0
2
Order By: Relevance
“…Additionally, infections are risk factors for development of some forms of non-infectious lung injury which may occur later, such as IPS (Versluys, 2010). Importantly, infections with bacterial, viral, and fungal pathogens can afflict both allogeneic and autologous HSCT recipients at multiple times post-transplant (Afessa and Peters, 2006; Lim, 2006). …”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…Additionally, infections are risk factors for development of some forms of non-infectious lung injury which may occur later, such as IPS (Versluys, 2010). Importantly, infections with bacterial, viral, and fungal pathogens can afflict both allogeneic and autologous HSCT recipients at multiple times post-transplant (Afessa and Peters, 2006; Lim, 2006). …”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…Pulmonary complications (PCs) are among the most common and lethal complications suffered by hematopoietic SCT (HSCT) patients. [1][2][3][4] The increasing number of indications and the selection of more debilitated patients as potential candidates for HSCT seem to be changing the epidemiology of PC. 5,6 Studies have shown that in immunocompromised patients an early identification of the etiology of PC improves survival.…”
Section: Introductionmentioning
confidence: 99%
“…BO and OP as LOPCs occurring more than 3 months after PBSCT are well documented, [1][2][3][4][5][6][7][8][9] whereas NSIP as an LOPC after PBSCT has not been fully investigated. To our knowledge, CT pathologic correlations of NSIP as an LOPC have not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Interstitial pneumonias as LOPCs after PBSCT are closely related to chronic graft-versus-host disease (GVHD), and they easily develop when chronic GVHD is not well controlled. [1][2][3][4] At the first admission, we reduced the dose of FK 506 because an opportunistic infection was strongly suspected. The dose reduction of FK 506 might have caused cellular NSIP as a chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation